Análise dos efeitos de agrotóxicos sobre a espécie Scaptotrigona postica Latreille, 1807 - Orsi, Letícia (Universidade Federal de São Carlos, 2020)
Pollination is an important process for maintaining biodiversity, and bees are the main pollinators of most natural environments. Among the species found in Brazil, is Scaptotrigona postica Latreille, 1807, a species with stunted, eussocial and belonging to the Trigonini tribe. Even though bees are considered of extreme importance, some actions are causing the population of these insects to decrease, as is the case of the exaggerated and mistaken use of pesticides. This study aimed to expose forage bees, orally, to sublethal concentrations isolated from the insecticide dimetoate and the fungicide azoxystrobin (acute and chronic exposure), and also to evaluate and compare the morphological changes caused in the midgut and Malpighian tubules by both types of exposure. The morphological analyzes were made from sections carried out in microtome, in different depths of the organs, which underwent double staining techniques using Hematoxylin and Eosin. The slides were analyzed taking into account the following changes in the organs: loss of cytoplasmic material, loss of brush border, elimination of cells to the lumen, loss of regenerative cell nests, cell swelling, cells with pycnotic nuclei, apocrine secretion and spherocrystals. For each observed change, a pre-established score value was used, which depends on the intensity of the change in the organ. From the results obtained, it was observed that acute and chronic exposure to sublethal concentrations of pesticides were able to cause changes in the parameters mentioned, in both organs, with the exception of apocrine and spherocrystal secretion. Thus, it is concluded that acute and chronic exposure to sublethal concentrations of dimethoate and azoxystrobin cause morphological changes in important organs involved in the metabolic route of pesticides in S. postica.
Analysis of the effects of pesticides on the species Scaptotrigona postica Latreille, 1807
Keywords: Dimetoato; Azoxistrobina; Intestino; Túbulos de Malpighi; Exposição aguda e crônica; Dimethoate; Azoxyxtrobin; Intestine; Malpighian tubules; Acute and chronic exposure; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS BIOLOGICAS